Evaluation and spatial-temporal evolution of water resources carrying capacity in Dongting Lake Basin - Zhenghua Deng (IWA Publishing, 2021)
A three-dimensional rating index system for water resources system–water environment system–socioeconomic system is constructed based on data from Hunan Dongting Lake Eco-environment Monitoring Center, Hunan Provincial Water Resources Bulletin, and Hunan Statistical Yearbook. The water resources carrying capacity (WRCC) of Dongting Lake Basin from 2009 to 2018 is evaluated by the TOPSIS model combined with analytic hierarchy process (AHP) and entropy weight, and then the temporal evolution and spatial distribution characteristics of the WRCC of the Dongting Lake Basin are analyzed. The results show that: (1) The WRCC in the Dongting Lake Basin decreases from a good level to a reasonable level during the period. Among them, the WRCC of the Ouchi River, Hudu River, and Songzi River Basins decreases significantly. (2) There are obvious spatial differences in the WRCC of the Dongting Lake Basin in 2018, the WRCC order is Lishui River, West Dongting Lake, Zijiang River, South Dongting Lake, Yuanshui River, Xiangjiang River, East Dongting Lake, Songzi River, Hudu River, Ouchi River, with scores of 0.586, 0.526, 0.472, 0.448, 0.416, 0.397, 0.393, 0.313, 0.306, and 0.304, respectively. Finally, some policy recommendations for improving the WRCC of the Dongting Lake Basin are proposed. HIGHLIGHTS According to the definition of water resources carrying capacity, its index evaluation system has been established.; The paper combines entropy method and TOPSIS method to comprehensively evaluate the change of water resources carrying capacity of Dongting Lake Basin during the last 10 years.; The countermeasures for coordinated development of water resources and society in the Dongting Lake Basin are proposed.;